(untitled) (Journal of Partial Differential Equations, 2003)
" In this paper, we study the Morrey regularity of solutions to the de- generate elliptic equation -(a_iju_xi)_xj = -(f_j)_xj in R^n. For this purpose, we introduce four weighted Morrey spaces in R^n."